Stable isotope composition of long and short term carbon pools can screen drought tolerance in cassava - Van Laere, Jonas; Martinez Maya, Maria Alejandra; Selvaraj, Michael Gomez; Becerra-Lopez-Lavalle, Luis Augusto; Guzmann, Diego; Casas, Jorge Andres; Merckx, Roel; Hood-Nowotny, Rebecca; Dercon, Gerd (Elsevier, 2024)
Leaf carbon isotope composition (δ13C) is a promising trait for assessing genotypic differences in responses to environmental stress, particularly drought. Despite its potential, comprehensive evaluations of δ13C across various carbohydrate pools and leaf positions, in comparison with other traits, are still lacking for cassava (Manihot esculenta). This study aimed to estimate the genotypic effect size and the correlation with yield for δ13C and other commonly assessed traits in cassava. We compared the δ13C values at bulk root initiation stage of fourteen genotypes grown in the wet (1450 mm annual rainfall) and dry Caribbean (950 mm annual rainfall). We focused on both non-structural (soluble sugars) as well as structural (cellulose) carbohydrate pools across multiple leaf positions. Our results revealed significant genotypic effects across nearly all pools and leaf positions, which were equal or larger than other commonly measured traits. Interestingly, correlations between isotope composition and root yield were only observed in the dry location, with upper leaves exhibiting weaker correlations across all carbohydrate pools. Notably, while soluble sugars displayed stronger correlations with yield, they also demonstrated higher susceptibility to within-field variations. Furthermore, complementary information was found when combining δ13C with other traits such as leaf retention. Combining isotope compositions across various carbohydrate pools may reveal insights into source-sink dynamics. These results underscore the potential of δ13C as a tool for improving drought tolerance in cassava and provide a basis for its integration into cassava breeding programs, when used under dry conditions. To enhance the practical utility of δ13C as a screening technique, further research is advised to validate these findings across multiple locations, growing seasons and growth stages.